2017
DOI: 10.1177/1076029617703482
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Independent Survival Predictor in Pulmonary Embolism: Prognostic Nutritional Index

Abstract: The prognostic impact of nutritional status in patients with pulmonary embolism (PE) is poorly understood. A well-accepted nutritional status parameter, prognostic nutritional index (PNI), which was first demonstrated to be valuable in patients with cancer and gastrointestinal surgery, was introduced to patients with PE. Our aim was to evaluate the predictive value of PNI in outcomes of patients with PE. We evaluated the in-hospital and long-term (53.8 ± 5.4 months) prognostic impact of PNI on 251 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 23 publications
4
25
0
1
Order By: Relevance
“…Instead, since medium- and long-term follow-up mortality is mainly driven by comorbidities, CCI represent the most appropriate predictor of death, whith sPESI losing its prognostic value. These data are in keeping with other studies' results which found that in PE patients mortality was associated with variables not strictly related to the acute index event, such as plasma osmolality and nutritional indexes [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Instead, since medium- and long-term follow-up mortality is mainly driven by comorbidities, CCI represent the most appropriate predictor of death, whith sPESI losing its prognostic value. These data are in keeping with other studies' results which found that in PE patients mortality was associated with variables not strictly related to the acute index event, such as plasma osmolality and nutritional indexes [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Albumin levels in tertile 1 were also significantly lower than in tertile 3. As a result, they demonstrated that serum albumin-based prognostic nutritional index was an independent prognostic factor for mortality in patients with PE [29]. Our results for negative acute-phase reactant albumin were similar to these studies, and there was a significant decrease in serum albumin level for non-survival patients, which indicated it as a prognostic biomarker for PE disease.…”
Section: Discussionsupporting
confidence: 87%
“…Hayıroğlu et al [29] evaluated the prognostic nutritional index in PE. According to the classification, prognostic nutritional index patients in tertile 1 was 8.1 times higher.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the inflammatory hypothesis based GPS, prognostic nutritional index (PNI) was also reported to have potential value in predicting adverse outcomes of pulmonary thromboembolism (Hayıroğlu et al, 2018). Therefore, in the future, combining the results of multiple prognosis scores may help patients with AMI to better avoid adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%